Octamer-primed sequencing technology: effects of dNTP supplementation - Kraltcheva, A. I. (Oxford University Press, 2001)
Octamer-primed sequencing is a directed DNA sequencing strategy that employs the use of a presynthesized octamer primer library. Together with electronic octamer sequencing technology (eOST) it provides a faster, less expensive way to obtain DNA sequence information and can be used as a valuable tool for gap closure in large-scale genomic sequencing. In this paper we discuss the effect of dGTP/TTP supplementation on octamer sequencing. We show that addition of 75 µM dGTP and 5 µM TTP can improve the sequencing success rate by increasing the length and accuracy of generated sequence information. We also discuss the effect of template base composition immediately downstream of the octamer primer on the outcome of octamer sequencing.